Synthesis and Characterization of Trimethylchlorosilane-Modified Silica Xerogel - Sellen Tanheitafino; Anis Shofiyani; Risya Sasri; Rudiyansyah Rudiyansyah (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2020)
Modification of silica xerogel with TMCS (trimethylchlorosilane) reagent has been carried out to improve the hydrophobicity of silica xerogel. Silica xerogel was synthesized based on the sol-gel method using sodium silicate as a precursor, and citric acid as a catalyst, with a mole ratio of sodium silicate and citric acid, was 0.172: 0.004. The sol-gel process was carried out through several stages, i.e., hydrolysis and condensation of sodium silicate to form sol, gelation (sol transition to gel), aging, and drying. Surface modification was performed by studying the effect of TMCS: methanol: petroleum benzine volume ratio of 0.5:1:1, 1:1:1, 1.5:1:1, 2:1:1, and 2.5:1:1 on the characteristics of silica xerogel synthesized. FTIR, SEM, and GSA characterized the synthesized results. The results of FTIR characterization on silica xerogel with volume ratios of 2:1:1 and 2.5:1:1 indicate the presence of the Si‑C group absorption at a wavenumber of 848.68 cm-1 which shows that the formation of silyl groups on the modified silica xerogel surfaces occurs at a TMCS: methanol: petroleum benzine ratio of 2:1:1 and 2.5:1:1. SEM results indicate that the silica xerogels produced are porous. Meanwhile, the GSA analysis results show that the pore size distributions are in the mesoporous region with an average pore radius of 8-13 nm. The greater the volume of TMCS used, the higher the surface area, and the resulting xerogel’s hydrophobicity. Based on the contact angle and seeped time test, the highest hydrophobicity is produced by the material synthesized at a TMCS: methanol: PB volume ratio of 2.5:1:1 with a contact angle of 116.346°.